Application of a Physiologically Based Pharmacokinetic Approach to Predict Theophylline Pharmacokinetics Using Virtual Non-Pregnant, Pregnant, Fetal, Breast-Feeding, and Neonatal Populations - Abduljalil, Khaled; Gardner, Iain; Jamei, Masoud (Frontiers in Pediatrics, 2022)
Perinatal pharmacology is influenced by a myriad of physiological variables that are changing dynamically. The influence of these covariates has not been assessed systemically. The objective of this work is to use theophylline as a model drug and to predict its pharmacokinetics before, during (including prediction of the umbilical cord level) and after pregnancy as well as in milk (after single and multiple doses) and in neonates using a physiological-based pharmacokinetic (PBPK) framework model. Predicted infant daily doses were calculated using theophylline average and maximum concentration in the milk as well as an estimate of milk consumption. Predicted concentrations and parameters from the PBPK model were compared to the observed data. Neonatal theophylline exposure from milk consumption was projected in normal term and preterm subjects. PBPK predicted theophylline kinetics in non-pregnant and pregnant population at different gestational age were within 2-fold of the observations and observed concentrations fell within 5th – 95th prediction interval. The PBPK model predicted an average cord-to-maternal plasma ratio of 0.96, which also agrees with experimental observations. Predicted postpartum theophylline concentration profiles in milk were also in a good agreement with observations with a predicted milk-to-plasma ratio of 0.76. For an infant of 2.0 kg and consuming 150 mL of milk per day, the lactation model predicted a relative infant dose (RID) of 17% and 12% using predicted maximum (Cmax,ss) and average (Cavg,ss) concentration in milk at steady state. The maximum RID of 17% corresponds to an absolute infant daily dose from of 1.4±0.5 mg/kg/day. The amount projected, when administered as daily oral dose of 0.233 mg/kg/ given every 4h, to resemble breastfeeding frequency, to a virtual preterm neonate population aged 32 GWs at birth, yielded neonatal plasma concentrations of 8.5 (4-15) mg/L (mean (5th-95th percentiles). A lower plasma level of 5.7 (2.5-10) mg/L was predicted for a full-term neonate population at birth with the same dosing protocol.